2006
DOI: 10.1111/j.1742-1241.2006.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of intraoperative abdominal cavity culture in appendicectomy: a retrospective study

Abstract: Appendicectomy is one of the most common surgical emergency procedures. Intraperitoneal culture during appendicectomy is routine practice in some hospitals, while some surgeons advocate abandoning this routine. The aim of our study is to determine the value of intraoperative abdominal cavity culture and its impact on the patient management. Retrospective analysis was performed on 498 patients who underwent appendicectomy over 2.5-year period. The median of the postoperative hospital stay was 2 days, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…However, the patient was treated with Tazocin, an antibiotic that was not listed on the sensitivities obtained from the pus samples. The results of this study suggests that obtaining routine pus samples in complicated appendicitis for cultures and sensitivity can be abandoned which is similar to findings in previous literature (4,5,(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 89%
“…However, the patient was treated with Tazocin, an antibiotic that was not listed on the sensitivities obtained from the pus samples. The results of this study suggests that obtaining routine pus samples in complicated appendicitis for cultures and sensitivity can be abandoned which is similar to findings in previous literature (4,5,(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 89%
“…48,49 Several studies have shown that routine peritoneal fluid cultures as a means of directing patient-specific antibiotic therapy have no clinical usefulness. [50][51][52][53][54] However, in our survey, most of respondents declared that they send cultures from the intraperitoneal cavity. This could be due to the resistance that bacteria causing appendicitis have toward common antibiotic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain studies caused the continuation of peritoneal swap application. In the absence of data coming from peritoneal cultures, current condition and variations in infectivity emphasized the inhibition of a predictable guide for empiric antimicrobial therapy in the future [16,17]. In various studies, the use of intraoperative peritoneal swap routinely and properly might provide significant and instructive data, and the necessity of peritoneal fluid culturing was stated in the presence of visible inflammation or in high-risk patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, the use of intraoperative peritoneal swap routinely and properly might provide significant and instructive data, and the necessity of peritoneal fluid culturing was stated in the presence of visible inflammation or in high-risk patients [15]. Moawed et al suggested the use of peritoneal culture for the epidemiological follow-up of rarely isolated microorganisms that are responsible for severe diseases, the benefit of peritoneal swap and a proof for the susceptibility of microbial antibiotic were reported in complex individual patients [16]. In a study conducted by Solomkin et al, it was recommended to sample in perforated appendicitis and other communityacquired intraabdominal infections in case of a resistance problem of frequently detected isolated against common antibiotics (resistance 10% to 20%) in community, and it would be beneficial to detect epidemiological variations and post-discharge therapy choice in case of continuation of routine culturing in low-risk community-acquired intraabdominal infections [18].…”
Section: Discussionmentioning
confidence: 99%